Gender differences in financial advice - Tabea Bucher-Koenen; Andreas Hackethal; Johannes Koenen; Christine Laudenbach (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We show that financial advisors recommend more costly products to female clients, based on minutes from about 27,000 real-world advisory meetings and client portfolio data. Funds recom-mended to women have higher expense ratios controlling for risk, and women less often receive rebates on upfront fees for any given fund. We develop a model relating these findings to client stereotyping, and empirically verify an additional prediction: Women (but not men) with higher financial aptitude reject recommendations more frequently. Women state a preference for delegat-ing financial decisions, but appear unaware of associated higher costs. Evidence of stereotyping is stronger for male advisors.
Keywords: G2; E2; D8; 330; credence goods; financial aptitude; consumer protection; financial literacy; discrimination